Development of Theranostic Cationic Liposomes Designed for Image-Guided Delivery of Nucleic Acid - Hai Doan Do; Christine Ménager; Aude Michel; Johanne Seguin; Tawba Korichi; Hélène Dhotel; Corinne Marie; Bich-Thuy Doan; Nathalie Mignet (MDPI AG, 2020)
Cationic liposomes have been considered as potential vectors for gene delivery thanks to their ability to transfect cells with high efficiency. Recently, the combination of diagnostic agent and therapeutic agents in the same particle to form a theranostic system has been reported. Magnetic liposomes are one of these examples. Due to the magnetic nanoparticles encapsulated in the liposomes, they can act as a drug delivery system and, at the same time, a magnetic resonance imaging contrast enhancement agent or hyperthermia. In this work, nucleic acid delivery systems based on magnetic cationic liposomes (MCLs) were developed. Two different techniques, reverse phase evaporation and cosolvent sonication, were employed for liposome preparation. Both strategies produced MCLs of less than 200 nm with highly positive charge. Enhancement of their transverse and longitudinal relaxivities r2 and r1 was obtained with both kinds of magnetic liposomes compared to free magnetic nanoparticles. Moreover, these MCLs showed high capacity to form complexes and transfect CT-26 cells using the antibiotic-free pFAR4-luc plasmid. The transfection enhancement with magnetofection was also carried out in CT26 cells. These results suggested that our MCLs could be a promising candidate for image-guided gene therapy.